Answers

You'll need to make use of the following three results.
If y = x^a then dy/dx = a*x^(a-1). This is valid for any value of a including 1/2.
Product rule. Suppose y has the form of one function of x, say x^3, multiplied by another function of x, say sin(x). Then we can write this as:
y = u*v
Where we have defined u = x^3 and v = sin(x).
Then the product rule states that:
dy/dx = (du/dx)v + (dv/dx)u
That is, take the derivative of each part of the product separately and multiply the result by the other part, and add these together. For a simple example, take the derviative of x^3. We could just do this in one go using (1), but suppose we write x^3 = (x^2)*x. Then, using the product rule with u = x^2 and v = x:
dy/dx = [d(x^2)/dx]x + (dx/dx)x^2
dy/dx = 2x^2 + x^2
dy/dx = 3x^2.
3) Chain rule, "function of a function". Look at the second part of the expression you gave. We see that the entire expression 2x+1 is raised to the power 1/2. We could call this the function "to the power 1/2" of the function "2x+1". Hence the "function of a function". To differentiate this, write 2x+1 = f and y = f^1/2. Then:
dy/dx = (dy/df)*(df/dx)
For dy/df you'll get (1/2)f^(-1/2) using rule 1. You must replace f by its value in terms of x, ie (1/2)*(2x+1)^(-1/2). Meanwhile df/dx is just 2, so dy/dx becomes (2x+1)^(-1/2).
Now you need to put all these parts together, using the result at the end of part 3 and applying the product rule to the whole equation.
Hope this is clear, there's a lot to take in.
James

05 September 2012

(3x²-8x+9)²

15 October 2020

Add an answer

Similar questions